2017
DOI: 10.3389/fimmu.2017.00611
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Domain of Hemocyanin, a Major Antimicrobial Protein from Litopenaeus vannamei: Structural Homology with Immunoglobulins and Molecular Diversity

Abstract: Invertebrates rely heavily on immune-like molecules with highly diversified variability so as to counteract infections. However, the mechanisms and the relationship between this variability and functionalities are not well understood. Here, we showed that the C-terminal domain of hemocyanin (HMC) from shrimp Litopenaeus vannamei contained an evolutionary conserved domain with highly variable genetic sequence, which is structurally homologous to immunoglobulin (Ig). This domain is responsible for recognizing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 81 publications
(107 reference statements)
0
38
1
Order By: Relevance
“…Strategies managing antibiotic-resistant bacteria include antibioticindependent and -dependent methods. The antibioticindependent method includes vaccines, metabolomereprogramming molecules, phage therapy and antibacterial peptides (Peng et al, 2015a;Du et al, 2017;Pires et al, 2017;Wang et al, 2017;Zeng et al, 2017;Zhang et al, 2017;Jiang et al, 2019). Vaccines stimulate the host's active immunity against bacterial pathogens (Guo et al, 2018;Cheng et al, 2018a;Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies managing antibiotic-resistant bacteria include antibioticindependent and -dependent methods. The antibioticindependent method includes vaccines, metabolomereprogramming molecules, phage therapy and antibacterial peptides (Peng et al, 2015a;Du et al, 2017;Pires et al, 2017;Wang et al, 2017;Zeng et al, 2017;Zhang et al, 2017;Jiang et al, 2019). Vaccines stimulate the host's active immunity against bacterial pathogens (Guo et al, 2018;Cheng et al, 2018a;Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…All these suggest that the Ig‐like domain of hemocyanin possessed immunology function. Further evidence indicated that the Ig‐like domain of hemocyanin could interact with bacteria and had agglutination activity toward E. coli K12, compared with the other domains of hemocyanin . Aside from this, we also previously showed that an 18.4 kDa peptide on the C terminus of small subunit hemocyanin (double underlined in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Our previous studies showed that the Ig‐like domain of Penaeus vannamei hemocyanin could react with anti‐human Ig and was also significantly upregulated during Taura syndrome virus infection . All these suggest that the Ig‐like domain of hemocyanin possessed immunology function.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations